Institutional Change and the Transformation of Interorganizational Fields: An Organizational History of the U.S. Radio Broadcasting Industry - Leblebici, Huseyin; Salancik, Gerald R.; Copay, Anne; King, Tom (Administrative Science Quarterly, 1991)
Huseyin Leblebici, Gerald R. Salancik, Anne Copay, Tom King, Institutional Change and the Transformation of Interorganizational Fields: An Organizational History of the U.S. Radio Broadcasting Industry, Administrative Science Quarterly, Vol. 36, No. 3 (Sep., 1991), pp. 333-363